Polarized light and optical measurement - Clarke, D. (David), 1936-; Grainger, J. F. (John Fraser), 1936- (International series of monographs in natural philosophy, 1971)
Polarized Light and Optical Measurement is a five-chapter book that begins with a self-consistent conceptual picture of the phenomenon of polarization. Chapter 2 describes a number of interactions of light and matter used in devising optical elements in polarization studies. Specific optical elements are given in Chapter 3. The last two chapters explore the measurement of the state of polarization and the various roles played in optical instrumentation by polarization and polarization-sensitive elements. This book will provide useful information in this field of interest for research workers,